Array comparative genomic hybridization and flow cytometry analysis of spontaneous abortions and mors in utero samples - Buysse Karen; Janssens Sandra; Chiaie Barbara; Swerts Katrien; Menten Björn; Philippé Jan; Speleman Frank (BMC, 2009)
Abstract Background It is estimated that 10-15% of all clinically recognised pregnancies result in a spontaneous abortion or miscarriage. Previous studies have indicated that in up to 50% of first trimester miscarriages, chromosomal abnormalities can be identified. For several decades chromosome analysis has been the golden standard to detect these genomic imbalances. A major drawback of this method is the requirement of short term cultures of fetal cells. In this study we evaluated the combined use of array CGH and flow cytometry (FCM), for detection of chromosomal abnormalities, as an alternative for karyotyping. Methods In total 100 spontaneous abortions and mors in utero samples were investigated by karyotyping and array CGH in combination with FCM in order to compare the results for both methods. Results Chromosome analysis revealed 17 abnormal karyotypes whereas array CGH in combination with FCM identified 26 aberrations due to the increased test success rate. Karyotyping was unsuccessful in 28% of cases as compared to only two out of hundred samples with inconclusive results for combined array CGH and FCM analysis. Conclusion This study convincingly shows that array CGH analysis for detection of numerical and segmental imbalances in combination with flow cytometry for detection of ploidy status has a significant higher detection rate for chromosomal abnormalities as compared to karyotyping of miscarriages samples.